مشاكل النقل البحري في المقاطعات الإفريقية ودور الرومان في حلها ما بين (27ق.م -284م). Problems Of Transport Marine In The African Provinces And The Role Of The Romans In Solving Between (27b.c-284a .d). - بخضرة, عبد القادر (University of Eloued جامعة الوادي, 2021)
ملخص: لعب نشاط النقل في توسع المستعمر الروماني على حساب الكثير من المقاطعات ومنها الإفريقية ، وساهم كذلك في استغلال خيرات المقاطعة ونقلها للعاصمة روما من اجل تموين سكانها ،إلا ان هذا النشاط اكتنفته مجموعة من الصعوبات التي و واجها الرومان منها الطبيعية التي صعبت الملاحة، أو القراصنة الذين عرقلوا السير الحسن للسفن الرومانية بالسواحل الإفريقية ،إضافة لنوعية السفن وسرعتها وحمولتها وانعكاساتها على النقل البحري والناقلين بصفة خاصة ،والأكثر من هذا المشاكل المهنية المختلفة كسوء تعامل الإدارة الرومانية مع الناقلين خاصة الأفارقة واهتمامها فقط بعدم توقف نشاط النقل والصعوبات المالية وبالمقابل عند كل مشكل تطرقنا غلى الحلول المتخذة في ذلك. الكلمات المفتاحية: إفريقيا الرومانية ؛ الملاحة؛ الظروف الطبيعية ؛القرصنة؛ نوعية السفن والحمولة؛ المخاطر المهنية. Abstract: The transport activity played in the expansion of the Roman colonialist at the expense of many provinces, including Africa, and also contributed to the exploitation of the province’s resources and transporting them to the capital, Rome, in order to supply its inhabitants. However, this activity was beset by a set of difficulties that the Romans faced, including the natural ones that made navigation difficult, or the pirates who They hindered the smooth running of Romanian ships on the African coasts, in addition to the quality of the ships, their speed, their tonnage, and their implications for maritime transport and carriers in particular, and more than this various professional problems such as the Roman administration’s mishandling of the transporters, especially the Africans, and its concern only for not stopping transport activity and financial difficulties and in return for every problem we dealt with solutions Taken in it.
مقال